Pengaruh CAR, NPL, dan LDR Terhadap ROE Pada Perusahaan Perbankan Yang Terdaftar di BEI Tahun 2023 - Satriandi , Meiludin Putra; Yulia, Iis Anisa; Pranamulia, Agus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), and Loan to Deposit Ratio (LDR) on Return on Equity (ROE) in banking companies listed on the Indonesia Stock Exchange (IDX) in 2023. The sample consists of 19 banking companies selected based on specific criteria using purposive sampling, a method categorized under non-probability sampling. Hypothesis testing was conducted using multiple linear regression analysis. The results indicate that CAR and NPL have a significant partial effect on ROE, while LDR has no significant effect on ROE. The F-test results show that CAR, NPL, and LDR collectively have a significant effect on ROE.